1999
DOI: 10.1111/j.1365-2621.1999.tb15939.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Production of Enterotoxin A by Staphylococcus aureus on “Home‐style” French Fries

Abstract: Staphylococcus aureus strains were inoculated onto freshcut oil-blanched potato strips stored at 21 or 26.7 °C for up to 9 h to determine if the microorganism was capable of growth and staphylococcal enterotoxin (SE) production. Potato strips were assayed for SE using a commercial ELISA kit prior to and following finish frying. S. aureus increased by 2.5 to 2.8 log CFU/g over 9 h at 26.7 °C, and SE was detected after 5 h. SE remained serologically detectable following finish frying of the potato strips. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…(Arkoudelos, Samaras, & Tassou, 2003;Inatsu, Bari, Kawasaki, & Isshiki, 2004;Vora, Senecal, & Schaffner, 2003). It has been demonstrated that for detectable SE production in food samples between 10 5 and 10 7 CFU/g S. aureus population is required (Doan & Davidson, 1999;Fujikawa & Morozumi, 2006). Specific quantification of SEs from the raw food products using molecular tools (e.g., real time immuno-PCR, enzyme immunoassay, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…(Arkoudelos, Samaras, & Tassou, 2003;Inatsu, Bari, Kawasaki, & Isshiki, 2004;Vora, Senecal, & Schaffner, 2003). It has been demonstrated that for detectable SE production in food samples between 10 5 and 10 7 CFU/g S. aureus population is required (Doan & Davidson, 1999;Fujikawa & Morozumi, 2006). Specific quantification of SEs from the raw food products using molecular tools (e.g., real time immuno-PCR, enzyme immunoassay, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…According to the U.S. Food and Drug Administration (FDA), ≥10 5 CFU/g S. aureus is capable of causing staphylococcal intoxication. It has been demonstrated that for detectable SE production in food samples, a S. aureus population between 10 5 and 10 7 CFU/g is required (Doan and Davidson 1999; Fujikawa and Morozumi 2006; Huong and others 2010). The CPS counts were above the maximum tolerable microbiological limit (10 3 CFU/g‐mL) for some of the dairy products evaluated in this study according to the Turkish Food Codex (Anonymous 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The TECRA kit came with a color card that was used to match the green color that developed in individual wells. The optical density of the developed color in each well according to the concentration of SEs was measured at 414 nm using an ELISA reader, and then the optical density was compared to a standard curve to determine the concentration of SEs in each sample (Doan and Davidson ; Min et al . ).…”
Section: Methodsmentioning
confidence: 99%